Small medium enterprises' resources and the development of innovation in Malaysia - Abu Bakar, Lily Julienti; Ahmad, Hartini (IBIMA Publishing, 2010)
More recent research has shifted attention from tangible to intangible resources as it perceived to be more important from a strategic point of view, since they bring together more frequently the requirements necessary for producing sustainable advantage: to be valuable, rare and difficult to imitate and replace by competitors (Barney 1991; Hitt et al. 2001).In view of the fact that there has been a dramatic increase in Malaysia SMEs development, this research reviews the SME resources and its contribution to innovation development. In the context of Malaysia manufacturing companies, reputational resources have been found given the highest impact on the product innovation performance compared to other factors.Survey was distributed randomly to the business owners and managers who work in various sizes of manufacturing firms.The response rate was 48% resulted from the personally administered questionnaire are considered highly favorable.